Evaluation of markets for irrigation water in the internal river basins of Catalonia, Spain - Pujol, J.; Berbel, J.; Ramírez de Cartagena, F.; Viaggi, D.; Raggi, M. (Spanish Journal of Agricultural Research, 2006)
Irrigated agriculture has come under close scrutiny in Europe recently because of its high share of total water consumption and its apparent inefficiency. Several water policies have been advocated, in particular the use of economic instruments such as water markets. This paper simulates the impact of a policy based upon water markets on agricultural production in the internal river basins of Catalonia (Spain). This zone presents certain particularities that make it very interesting to study: competition between sectors for the resource (agriculture-urban consumption-recreational uses), recent periods of resource insufficiency and conflicts between irrigators as a result of the measures taken by the hydraulic administration in drought situations. The results show that these markets would guarantee an optimal reassignment of the resource in situations of supply restrictions, and although compared to the situation without markets they would not mean higher economic profits for the irrigators, they could prevent conflicts between them. Nevertheless, doubts exist about their acceptance by irrigators.